2019
DOI: 10.1101/702704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blocking neuroestrogen synthesis modifies neural representations of learned song without altering vocal imitation accuracy in developing songbirds

Abstract: Birdsong, like human speech, is learned early in life by first memorizing an auditory model. Once memorized, birds compare their own burgeoning vocalizations to their auditory memory, and adjust their song to match the model. While much is known about this latter part of vocal learning, less is known about how initial auditory experiences are formed and consolidated. In both adults and developing songbirds, there is strong evidence suggesting the caudomedial nidopallium (NCM), a higher order auditory forebrain… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 141 publications
0
1
0
Order By: Relevance
“…We were also surprised to see that chronic exemestane treatment in females caused some females to produce 1-2 repeated syllables in a song-like manner, even though they had atrophied song nuclei. Prior studies have shown that acute aromatase inhibition can suppress the rate of singing in zebra finches and canaries (Alward et al, 2016;Vahaba et al, 2019;Walters and Harding, 1988), but no changes in song learning acuity have been reported (Merten and Stocker-Buschina, 1995;Vahaba et al, 2019). Perhaps the more potent and longterm application of the estrogen inhibitor we used revealed an unknown involvement of estrogen in vocal learning.…”
Section: Discussionmentioning
confidence: 82%
“…We were also surprised to see that chronic exemestane treatment in females caused some females to produce 1-2 repeated syllables in a song-like manner, even though they had atrophied song nuclei. Prior studies have shown that acute aromatase inhibition can suppress the rate of singing in zebra finches and canaries (Alward et al, 2016;Vahaba et al, 2019;Walters and Harding, 1988), but no changes in song learning acuity have been reported (Merten and Stocker-Buschina, 1995;Vahaba et al, 2019). Perhaps the more potent and longterm application of the estrogen inhibitor we used revealed an unknown involvement of estrogen in vocal learning.…”
Section: Discussionmentioning
confidence: 82%